Pharmaceutical pollution of aquatic environment: an emerging and enormous challenge - Rzymski Piotr; Drewek Agnieszka; Klimaszyk Piotr (Limnological Review, 2017)
The global use of pharmaceuticals is on the systematic rise and leads to contamination of surface waters with xenobiotic compounds with a wide range of bioactivity. Waters that receive urban and medical effluents are particularly threatened. The presence of pharmaceuticals in these ecosystems can lead to unpredictable ecological impacts and responses, and may also have an impact on human health. At the same time the identification and quantification of these chemicals, to a large extent remains a subject to scientific investigation than part of a thorough monitoring programme. Their biological effects on aquatic organisms are mainly recognized experimentally and often using concentrations far exceeding environmentally relevant levels. This review paper defines the main sources of pharmaceuticals in the aquatic environment, discusses the fate of these compounds and summarizes the current state-of-the-art of pharmaceutical monitoring in Polish surface waters.